Lisbonne, Tolède, Madrid - Manuelle Peloille (Catalonia)
Ernesto Giménez Caballero’s book, Amor a Portugal, traces Franco’s State visit in October 1949. The author recycles the thesis of the Portuguese traditionalist thinkers Oliveira Martins and Sardinha, which consists in defending the Luso-Spanish model of colonization against the model of Anglo-Saxon neo-colonialism. During the years 1890-1920, Spain and Portugal had to reconsider their place in the imperialist world. In 1949, the beginning of the Cold War forced the two countries to redefine themselves, without abandoning their general line of Atlantic Peninsular alliance.